Requirement Analysis of E-Counseling System for Matriculation College - Hasbullah, Osman (2010)
Nowadays, there are numbers of higher education institutions in Malaysia provided online counseling service as the alternative way for students who are facing difficulties to attend to the counseling center or have problems to face the counselors. With the existence of online counseling service, it helps students in solving problems regarding their study or personal life. From the observations done on the internet, public matriculation colleges in Malaysia have not provided online counseling service for students. Therefore, the purpose of this project is to construct a requirement model for online counseling service for students and counselors' usage in matriculation colleges. Requirement model is one technique used to identify the requirements of one particular system based on user's needs and features of related existed system. Next, it designs and constructs the system based on the constructed requirement model. UML notation has been used in this project in order to build the requirement model for online counseling service and system prototype design is designed in storyboard form. In this project, the functions of the system prototype have been discussed in detail based on the constructed requirement model.